PERAN PEMERINTAH DAERAH KABUPATEN KENDAL DALAM PENGEMBANGAN PELABUHAN KENDAL - Bestyaning Sekti Widodo; Turtiantoro - - (Journal of Politic and Government Studies, 2020)
Kendal Port is a transfer of passenger and crossing sea port activities in the Port of Tanjung Emas Semarang, from the function, role and administration of the Kendal Port are under the auspices of the Port of Tanjung Emas Semarang. The development of Kendal Port into a commercial port utilizes the potential of the strategic location of the Kendal Regency, which is mainly close to Semarang City. This research discusses the role of the Kendal District Government in the development of the Kendal Port. The purpose of this research is to describe more deeply the role of the Kendal District Government in the development of the Kendal Port. This research uses descriptive qualitative research methods with data collection techniques through interviews, documentation, and literature review conducted to relevant informants. The results of this research are describing various findings in the field related to the role of the Regional Government of Kendal Regency in the development of Kendal Port, namely the construction of various main and supporting infrastructure facilities at the port, the budgeting of the Kendal APBD, Central Java APBD, and the State Budget, the existence of a development cooperation plan between the Regional Government Kendal Regency with BUMN, and public participation that strongly supports to port development, as well as the various benefits obtained by the Kendal District Government and the Kendal society.